Amphiphilic porous polyhedral oligomeric silsesquioxanes (POSS) incorporated polyoxometalate-paired polymeric hybrids: interfacial catalysts for epoxidation reactions1. Issue 23 (13th March 2015) - Leng, Yan; Zhao, Jiwei; Jiang, Pingping; Wang, Jun
<x xml:space="preserve">Abstract</x> Amphiphilic porous POSS incorporated POM-paired polymeric hybrids were demonstrated to be highly efficient interfacial catalysts for epoxidation of alkenes with H2O2.